Pattern of Aerobic bacterial infections in Nephrotic children (Bangladesh Journal of Medical Microbiology, 2017)
100 nephrotic children were studied in the Microbiology Department of Dhaka Medical College, Dhaka, from January to December/ 2004. The mean age was 5.4 years (range 1-15 yrs.), 68 were male and the rest 32 were female. All children were diagnosed case of nephrotic syndrome having International Study of Kidney Diseases in Children (ISKDC) criteria with normal renal functions. The patients were monitored clinically presented with any infections as a complication of nephrotic syndrome and investigations were carried out accordingly. 59 patients were found to have various types of infections. Urinary tract infection (UTI) was the commonest and seen in 50 patients. Peritonitis and cellulitis were present in two patients each. The most common isolated organism was E.coli and Pseudomonas in urine. E.coli was mostly susceptible to Ciprofloxacin but resistant to Ceftriaxone. Pseudomonas was mostly resistant to ceftriaxone but susceptible to imipenem.Bangladesh J Med Microbiol 2017; 11 (1): 19-22